2016
DOI: 10.1155/2016/5918457
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of External Dacryocystorhinostomy in the Age of Transcanalicular Microendoscopic Techniques

Abstract: Purpose. This study aimed to evaluate long-term results of external dacryocystorhinostomy (DCR) at a tertiary eye care center specializing in lacrimal duct surgery in Germany. Methods. The medical records of 1010 patients with acquired nasolacrimal duct obstruction (NLDO), who had undergone lacrimal duct surgery at a tertiary eye care center, were reviewed. Only adult patients who had undergone external DCR were included. The evaluation included the following parameters: age, gender, duration of symptoms, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 17 publications
4
22
1
5
Order By: Relevance
“…This is similar to study conducted by M. Alnawaiseh et al, 2 in which patients with previous episodes of dacryocystitis had a success rate of 82.7% and those without previous episodes of dacryocystitis reported a success rate of 83.4%. Gilad et al 8 observed 94.4% success rate in patients with dacryocystitis and 86.7% in patients without such history ( = 0.337).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is similar to study conducted by M. Alnawaiseh et al, 2 in which patients with previous episodes of dacryocystitis had a success rate of 82.7% and those without previous episodes of dacryocystitis reported a success rate of 83.4%. Gilad et al 8 observed 94.4% success rate in patients with dacryocystitis and 86.7% in patients without such history ( = 0.337).…”
Section: Discussionsupporting
confidence: 91%
“…16,17 However, external DCR is a cost effective and equally efficacious procedure with similar success rates and is preferable in cases where endoscopic procedures are contraindicated and in previous failed surgeries. 2 In conclusion external DCR still remains the treatment of choice for NLDO in our setup with very good postoperative results in patients with or without previous history of dacryocystitis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…5 These procedures preserve the physiology of the lacrimal duct system and are a viable alternative to external procedures. 6 The advantages of endoscopic dacryocystorhinostomy over EX-DCR are better hemostasis, lack of scarring, shorter operating time and protection of the lacrimal pump mechanism.…”
mentioning
confidence: 99%